Using Action Research to Build Evaluation Capacity in Public Health Organizations - Isabelle Bourgeois; David Buetti (Journal of MultiDisciplinary Evaluation)
Background: New practice standards in Ontario require the ongoing evaluation of public health programs. However, public health units have limited capacity to conduct and use evaluations.